Academic Climate Reinforcement in An Effort of Establishing Start-ups Based on Student Business Determination - Abdul Aziz Bagis; Mahyudin Nasir (Universitas Negeri Malang, 2020)
This study aims to confirm the role of students' businessdetermination after completing entrepreneurship courses on productivebehavior by reinforcing the academic climate experienced by students andensuring the role of strong ideals and enthusiasm among students. Thisresearch primarily focused on students who have completedentrepreneurship courses in various study programs at the University ofMataram. The study involved students' attitudes in the form of determinationthat reflect the strong aspirations and enthusiasm of doing business and theirinfluence on efforts to realize entrepreneurial intentions, in establishing novel,creative, innovative and innovative technology-based startup. It alsomeasured how dare the students to take measurable risks. It comprehensivelyproved that student entrepreneurial behavior can be established on the basisof a strong desire to become entrepreneurs from the beginning of study, withthe support of business knowledge and skills and strengthening the academicclimate that creates psycho-social conditions such as academics.